Kajian Eko Interior Pada Hotel Budget di Balikpapan - Chelline Monica Gani (Intra, 2016)
Ecological approach in the planning and building design requirements that should be met by the perpetrators of physical development. Hotel is one example of a physical building. Now, the hotel concept "budget" became a new phenomenon for the city of Aberdeen. According to the government regulation number PM.53 / HM.001 / mpek / 2013 article 2, the standard business hotel aims to provide protection, either for safety, health, comfort, safety and convenience and environmental preservation. This study aims to raise awareness of the designer budget hotel, knowing the performance space at budget hotels and know the concept design budget hotel that is economical and healthy for users and the environment. This research method using qualitative methods, to discuss aspects and parameters proposed by Kusumarini (2007). The object of research using three hotels, namely Best Inn hotel, Mirama, Mutiara Indah. Results of the analysis showed that the performance space at a budget hotel in London has been quite good and there are ecological efforts on several aspects. The drawback is the water sanitation and waste management has not been a particular concern. The designer budget hotel building role in the implementation of eco-interior to form a pattern of healthy life.